A Theological Approach to Performance Management in Strengthening Modern Work Ethics in Educational Institutions - Ushansyah, Ushansyah; Hamdanah, Hamdanah; Mazrur, Mazrur (Sharia Journal and Education Center Publishing, 2025)
Islamic theology based performance management has emerged as a strategic approach to improving the quality of Islamic education in the contemporary era, particularly as institutions such as pesantren are required not only to transmit knowledge but also to cultivate character through exemplification and daily practices. The challenges of globalization, the need to strengthen work ethics, and the demand for enhancing the quality of Islamic educational institutions make the integration of kalam-derived theological values a relevant foundation for performance management. This article employs a descriptive qualitative method with a library research approach, analyzing literature related to performance management, Islamic theological values, and their implementation within Islamic educational institutions. Data were analyzed through processes of reduction, presentation, and conclusion drawing to reveal patterns of theological value integration in educational managerial practices. The findings indicate that performance management incorporating Islamic values such as honesty, responsibility, discipline, and collaboration effectively enhances the work ethic of teachers and students, strengthens organizational culture, and supports holistic character formation. Practical implementations, including maqaṣid al-shari‘ah based evaluation, the development of students’ soft skills, and teacher training grounded in Islamic values, positively influence the effectiveness of Islamic educational institutions. However, challenges such as insufficient training, limited facilities, and resistance to change must be addressed systematically. The implications of this study underscore the importance of reinforcing Islamic performance management policies, enhancing educator capacity, and fostering collaboration among schools, parents, and communities to develop Islamic educational institutions that are excellent, adaptive, and character-driven.